Hubungan Peran Orang Tua Dengan Tindakan Personal Hygiene Menstruasi Pada Remaja Putri di SMP Negeri 1 Sambirejo Sragen - Cindy Amelia Agustin; Witriyani Witriyani; Ikrima Rahmasari (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Personal hygiene during menstruation is a crucial aspect in maintaining the reproductive health of adolescent girls. Failure to adhere to personal hygiene practices during menstruation can potentially lead to various health problems, such as reproductive tract infections, pruritus vulvae, and vaginal discharge. Parents play a crucial role in shaping healthy behaviors in adolescent girls by providing education regarding the reproductive process and how to properly care for their genitals. Parents' roles in this context are considered effective if they actively provide reproductive health education, establish open communication, and model healthy behaviors. This education includes providing accurate information about reproductive organ function, techniques for cleaning genitalia during menstruation, and discussing health issues related to menstruation. This study aims to determine the relationship between parental role and menstrual personal hygiene practices among adolescent girls at SMP Negeri 1 Sambirejo, Sragen. The study used a quantitative method with a descriptive correlational design and a cross-sectional approach. The study sample consisted of 81 respondents, selected using a purposive sampling technique. The instruments used were questionnaires on parental roles and menstrual personal hygiene practices. The results showed that 53 respondents (65.4%) had parents with good roles, and 62 respondents (76.5%) had good menstrual personal hygiene practices. Data analysis using the Spearman Rank test resulted in a p value = 0.000 (p < 0.05), which indicates that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. Thus, there is a significant relationship between parental roles and menstrual personal hygiene practices in adolescent girls at SMP Negeri 1 Sambirejo. This finding underscores the importance of parents' role in supporting proper menstrual hygiene practices through providing accurate information, open communication, and examples of healthy behavior, thus contributing to the prevention of reproductive health disorders among adolescents.